An Original L‐shape, Tunable N‐Heterocyclic Carbene Platform for Efficient Gold(I) Catalysis. Issue 24 (8th May 2019) - Tang, Yue; Benaissa, Idir; Huynh, Mathieu; Vendier, Laure; Lugan, Noël; Bastin, Stéphanie; Belmont, Philippe; César, Vincent; Michelet, Véronique
Abstract: The synthesis and characterization of original NHC ligands based on an imidazo[1, 5‐ a ]pyridin‐3‐ylidene (IPy) scaffold functionalized with a flanking barbituric heterocycle is described as well as their use as tunable ligands for efficient gold‐catalyzed C−N, C−O, and C−C bond formations. High activity, regio‐, chemo‐, and stereoselectivities are obtained for hydroelementation and domino processes, underlining the excellent performance (TONs and TOFs) of these IPy‐based ligands in gold catalysis. The gold‐catalyzed domino reactions of 1, 6‐enynes give rise to functionalized heterocycles in excellent isolated yields under mild conditions. The efficiency of the NHC gold 5 Me complex is remarkable and mostly arises from a combination of steric protection and stabilization of the cationic Au I active species by ligand 1 Me . Abstract : Broadband ligands : The synthesis and characterization of original NHC ligands based on a imidazo[1, 5‐ a ]pyridin‐3‐ylidene (IPy) scaffold functionalized with a flanking barbituric heterocycle is described as well as their use as tunable ligands. High and unprecedented efficiency for gold‐catalyzed C−N, C−O, and C−C bond formations is disclosed.